Research of Fuzzy Recognition System of Working State of Hydraulic Support - ZHANG Shen; HUANG Huan; ZHAI Yan-rong; MA Xiu-ping; LIU Wei (Gong-kuang zidonghua, 2012)
In view of problem that current pressure monitoring system of hydraulic support of fully mechanized coal face can only monitor pressure of fully mechanized coal face and cannot recognize working state of hydraulic support, a fuzzy recognition system of working state of hydraulic support was designed. The system makes fuzzy recognition for pressure data monitored by existed pressure monitoring system of hydraulic support of fully mechanized coal face to judge five working states of hydraulic support, namely reducing support, advancing support, lifting support, increasing resistance and pressure relief keeping according to output of fuzzy recognition. When hydraulic support is in working state of increasing resistance and time of increasing resistance is too long, the system can real-timely notify operator to increase pressure of hydraulic support and assist to realize top coal breaking. The test result validated feasibility of the system.